Consensus Bundle on Maternal Mental Health: Perinatal Depression and Anxiety. Issue 3 (March 2017) - Kendig, Susan; Keats, John P.; Hoffman, M. Camille; Kay, Lisa B.; Miller, Emily S.; Moore Simas, Tiffany A.; Frieder, Ariela; Hackley, Barbara; Indman, Pec; Raines, Christena; Semenuk, Kisha; Wisner, Katherine L.; et al.
Abstract : Perinatal mood and anxiety disorders are among the most common mental health conditions encountered by women of reproductive age. When left untreated, perinatal mood and anxiety disorders can have profound adverse effects on women and their children, ranging from increased risk of poor adherence to medical care, exacerbation of medical conditions, loss of interpersonal and financial resources, smoking and substance use, suicide, and infanticide. Perinatal mood and anxiety disorders are associated with increased risks of maternal and infant mortality and morbidity and are recognized as a significant patient safety issue. In 2015, the Council on Patient Safety in Women's Health Care convened an interdisciplinary workgroup to develop an evidence-based patient safety bundle to address maternal mental health. The focus of this bundle is perinatal mood and anxiety disorders. The bundle is modeled after other bundles released by the Council on Patient Safety in Women's Health Care and provides broad direction for incorporating perinatal mood and anxiety disorder screening, intervention, referral, and follow-up into maternity care practice across health care settings. This commentary provides information to assist with bundle implementation. Abstract : The Council on Patient Safety in Women's Health Care Consensus Bundle on Maternal Mental Health supports routine screening for perinatal mood and anxiety disorders for pregnant and postpartum women.